Observance of Maqaasid and Urf and their Impact Contracts and Actions an Applied Jurisprudence Study: مراعاة المقاصد والعرف وأثرهما على العقود والتصرفات دراسة فقهية تطبيقية - Ali Mahdi Uthman, Ali Muhammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
يسلط البحث الضوء على أثر مراعاة المقاصد والنيات في العقود التي تقتضي الإيجاب والقبول من الطرفين كالبيع والإجارة والهبة والزواج إلى آخره، والتصرفات التي تقتضي وقوع الرضا من طرف واحد كالإبراء والإسقاط والطلاق، ويعالج البحث كثيرا من الإشكالات التي تقع – بحسن نية- أحيانا، وأحيانا أخرى تحت وطأة العرف الذي ينظر بعين الازدراء والاحتقار إلى من يخالف قواعده حتى ولو كان مطالبا بحقه الشرعي في ضوء مراعاة المقاصد الشرعية، ومواد القانون المدني المصري بما يساعد المفتين والقضاة على حل النزاع ورفع الإشكال بمنهجية علمية وفق الأحكام الشرعية. في هذا البحث رصد لكثير من الإشكالات العملية ووضع الحلول الفقهية العادلة لها، ومن هذه الصور: إنفاق الابن على الأسرة على ما جرت به العادة من غير تصريح بطلب المعاوضة ولا بالهبة ثم التنازع بعد ذلك في طلب العوض. مساهمة الزوجة براتبها في مسكن الزوجية، ثم طلب العوض عند النزاع. التوقيع على وثيقة الطلاق لا بقصد الفراق وإنما بغرض الحصول على معاش الوالد. التنازل عن الميراث خشية الازدراء من الأقارب. ومن أهداف البحث وضع الحلول الفقهية لكثير من الإشكالات العملية التي ترد إلى لجان الفتوى في موضوع البحث. التأكيد على مرونة الفقه، وقدرته على وضع الحلول العادلة لجميع مستجدات الحياة. استجابة لما نادى به مؤتمر الأزهر العالمي للتجديد في الفكر الإسلامي، من قدح زناد العقل الفقهي للخروج برؤى متطورة تبني على ما أصله الفقهاء السابقون لتضع الحلول العادلة لكثير من إشكالات العصر، وموضوع البحث أحد هذه الإشكالات. المنهج الذي سأتبعه في البحث- إن شاء الله- يتمثل فيما يلي: المنهج المقارن. منهج التحليل العلمي. منهج التخريج الفقهي. انتهى البحث إلى العديد من النتائج التي تدل على مراعاة مقاصد المكلفين في العقود والتصرفات وفق ضوابط شرعية تم بيانها تفصيلا في أثناء البحث، كما تم ذكر النتائج إجمالا في نهاية البحث. الكلمات المفتاحية: أثر، المقاصد، العرف، مراعاة، العقود والتصرفات. Abstract The research sheds light on the effect of observing purposes and intentions in contracts that require an offer and acceptance by both parties, such as selling, leasing, gift, marriage...etc, and behaviors that require consent from one party, such as acquittal, abolition and divorce. The research deals with many problems that sometimes occur - in good faith. And sometimes under the pressure of custom, which looks with contempt at those who violate its rules, even if they are claiming their legitimate right in light of observing the legitimate purposes, and the articles of the Egyptian Civil Code in a way that helps the muftis and judges to resolve the dispute and raise the problems with a scientific methodology in accordance with the legal provisions. Research problem: In this research, many practical problems have been monitored and the fair jurisprudential solutions have been developed for them.The son’s spending on the family on what is customary, without permission to ask for compensation or as a gift, then dispute after that in the request for compensation.The wife’s contribution with her salary to the marital home, and then asking for compensation in the event of a dispute.Signing the divorce document not for the purpose of separation, but for the purpose of obtaining the father's pension. Relinquishing the inheritance for fear of contempt from relatives Research aims: Develop jurisprudential solutions to many practical problems that are referred to the fatwa committees about the research. Emphasis on the flexibility of jurisprudence, and its ability to develop just solutions to all developments in life. In response to what was called by the Al-Azhar International Conference for Renewal of Islamic Thought, to ignite the trigger of the jurisprudential mind to come up with advanced visions that build on the origins of the previous jurists to put just solutions to many of the problems of the time, and the subject of research is one of these problems. Research Methodology: The method that I will follow in the research - God willing - is as follows: The comparative method. Scientific analysis method. Jurisprudence graduation curriculum. Research results: The research ended with many results that indicate the observance of the purposes of the taxpayers in contracts and actions according to legal controls that were detailed during the research, and the results were mentioned in general at the end of the research. Keywords: Impact, intentions, custom, observance, contracts, actions.